Decentralized Adaptive Control With Virtual Inertia for Cascaded-Type VSGs - Lang Li; Xiaochao Hou; Siqi Fu (IEEE Open Journal of Power Electronics)
This paper presents a decentralized adaptive control for cascaded-type virtual synchronous generators (CVSGs) in microgrids. By leveraging a frequency correction term derived from the local power derivative, the virtual inertia is adaptively adjusted without relying on phase-locked loops (PLLs), enabling a fully communication-free implementation. Compared to the existing methods, the need for PLLs is eliminated. The main novelty of the proposed method is the integration of adaptive inertia, PLL-free control and decentralization. Next, the stability of the proposed controller is assessed using the Lyapunov energy function method. Finally, its performance is validated through MATLAB/Simulink simulation and experiments.